2016
DOI: 10.1016/j.jasrep.2016.03.047
|View full text |Cite
|
Sign up to set email alerts
|

Dietary continuity vs. discontinuity in Bronze Age Italy. The isotopic evidence from Arano di Cellore (Illasi, Verona, Italy)

Abstract: This paper explores dietary practices in Bronze Age northern Italy through the isotopic investigation of human and animal collagen from the Early Bronze Age (EBA) necropolis of Arano di Cellore (Illasi, Verona). An earlier study had recently dated to the Bronze Age the introduction of C4 crops in the Po Plain in a way that makes this region of Europe a key area to explore Bronze Age economic strategies. Our study shows that diet at Arano was based on the consumption of C3 cereal-type plants, with isotope value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 38 publications
5
27
1
4
Order By: Relevance
“…BC) and of Arano di Cellore, Verona (2040-1890 cal. BC) support the hypothesis of C 4 plants consumption, and in particular of millet in some areas of the Verona province4546(Fig. 4).…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…BC) and of Arano di Cellore, Verona (2040-1890 cal. BC) support the hypothesis of C 4 plants consumption, and in particular of millet in some areas of the Verona province4546(Fig. 4).…”
Section: Discussionsupporting
confidence: 78%
“…4), confirming a preponderant C 4 plants based diet, Arano di Cellore (AC), dated to Early Bronze Age, shows a diet based on the consumption of C 3 cereal-type plants. Hence, the data from AC and ODN firmly place the shift in C 4 crop use in the region at a transition period between the late phases of the Early Bronze Age and the beginning of the Middle Bronze Age46, consequently our data show that successively, in pre-Roman times, the diet of most habitants of the zone was almost exclusively based on C 4 plants. This, indirectly indicates that this Celtic population had mastered agriculture techniques to such an extent that they could live off the harvest of their cultivated crops the year round.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Comparison with some earlier Bronze Age sites in the Veneto region such as Arano di Cellore (Varalli et al, ) and coeval contexts in southern regions of the Peninsula such as Toppo Daguzzo and Lavello (Tafuri et al, ) confirm that the consumption of C 4 crops was probably not a diffused practice in the Peninsula. There are still scarce isotope data on Bronze Age contexts outside the northern Peninsula, hence, comparison remains difficult.…”
Section: Discussionmentioning
confidence: 99%
“…There is a handful of isotopic studies on pre‐ and proto‐historic Italy (Lelli et al, ; Tafuri, Craig, & Canci, ; Tafuri et al, ; Varalli, Moggi‐Cecchi, Moroni, & Goude, ; Varalli et al, ), with northeastern Italy representing a critical area for the understanding of food practices of Early, Middle, and Late Bronze Age communities. In particular, earlier study by Tafuri et al () revealed the direct and possibly indirect consumption of C 4 plants (i.e., millets) at Olmo di Nogara, in the Po Plain, already at the middle phases of the Bronze Age (BM2 in local terminology), and isotope data from coeval contexts in southern Italy showed a fully C 3 ‐plant reliant diet.…”
Section: Introductionmentioning
confidence: 99%